Utilitarian and Deontological Approaches to Liability of Internet Intermediaries for Infringements of Intellectual Property Rights - Drakšas, Justinas (Teisė, 2024)
Internet intermediaries are the central figures through which the majority of informational flows go through on the Internet. It is therefore only natural to wonder, whether they should be held responsible, or even liable, for facilitating the exchange of illegal information being done by their users. Currently, academic literature focuses on two main views that could help to justify the imposition of liability on these subjects – these are the utilitarian and deontological theories of Internet intermediary liability. This paper attempts to deepen the understanding of these theories, by, firstly, identifying the main ideas behind the utilitarian and deontological approaches to the liability of Internet intermediaries; and secondly, looking at the main examples of regulation that are consistent with the utilitarian and deontological approaches, which could help to describe the overall evolution of intermediary liability models in the European Union.